EFFECT OF OPUNTIA ELATIOR ON CHOLESTEROL LEVEL ALTERATIONS INDUCED BY GAMMA RADIATION IN SWISS ALBINO MICE - POONIAM, KAVITA; SHARMA, JAIMALA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: Radiotherapy is deleterious to patient health by making the patient more susceptible to other diseases and often causes death by weakening the immune system and also affects cholesterol level. Based on these studies, it was moved toward the selection of Opuntia elatior as a herbal remedy for serum cholesterol level induced by gamma radiation. Methods: The modulatory effect of O. elatior stem extract was studied in Swiss albino mice at dose, i.e., 6 Gy of gamma radiation in the presence (experimental) or absence (control) of O. elatior extract (OEE) (10 mg/kg body weight) to observe in blood cholesterol level alterations. The animals were scarified and their blood was collected at days 1, 15, and 30 post-irradiation from heart puncture. Cholesterol level was estimated by the modified method of Roeschlau et al., 1974, using kit. Results: The cholesterol level was found almost constant in the control group (without any treatment) and increased in gamma radiation-treated group and decreased in only plant extract-treated group, whereas radiation-induced increased level of cholesterol was reduced by plant extract treatment in experimental animals (in plant extract with radiation-treated group), a normal level was achieved by day 30 post-treatment. Hence, O. elatior is beneficial to control radiation-induced blood cholesterol level. Conclusion: Radiation-induced side effects get lowered by herbal treatment and herbal products do not have their own side effects on body on their physical and chemical processes; thus, OEE is useful to manage blood cholesterol level as an edible part, it is easy to use as treatment and in my results OEE also support to maintain cholesterol level in serum of mice.